KAJIAN PENENTUAN LETAK SARINGAN PADA SUMUR BOR DAN DESAIN KONSTRUKSINYA DI AREA KAMPUS INSTITUT TEKNOLOGI SUMATERA (ITERA) - Bilal Al Farishi; Muhamad Ragil Setiawan; Wijayanti Ashuri (KURVATEK, 2019)
Clean water is a fundamental need for every kind of activities. ITERA as a university with various kind of learning activities cannot be separated from the need for clean water. Along with the rapid development of the campus, ITERA also requires a plan in order to provide clean water, one of which is by conducting a study of borehole construction design. This study was conducted because groundwater is one of the largest providers of clean water and must be managed properly. This study examines the shape of the construction and the right location of the filter on the borehole by looking at the geological and hydrogeological conditions and the position of the aquifer. Based on the study conducted, the geological conditions of the study area are in the Lampung Formation with the dominance of Tuff lithology. The position of the aquifer is found at a depth of 6.8 meters. Thus, the location of the filter in making bore wells should be at a depth of 20-25 meters and 40-50 meters. The filter made at these two depths is an anticipatory step if the groundwater drought during the dry season. Keywords: ITERA, clean water, aquifer, bore wells.